Black Political Organizations in the Post-Civil Rights Era - Stanford, Karin; Stanford, Karin; Johnson, Ollie; Johnson, Ollie (Book collections on Project MUSE., 2002)
We know a great deal about civil rights organizations during the 1960s, but relatively little about black political organizations since that decade. Questions of focus, accountability, structure, and relevance have surrounded these groups since the modern Civil Rights Movement ended in 1968. Political scientists Ollie A. Johnson III and Karin L. Stanford have assembled a group of scholars who examine the leadership, membership, structure, goals, ideology, activities, accountability, and impact of contemporary black political organizations and their leaders. Questions considered are: How have these organizations adapted to the changing sociopolitical and economic environment? What ideological shifts, if any, have occurred within each one? What issues are considered important to black political groups and what strategies are used to implement their agendas? The contributors also investigate how these organizations have adapted to changes within the black community and American society as a whole. Organizations covered include well-known ones such as the NAACP, Rainbow/PUSH Coalition, the Southern Christian Leadership Conference, the Urban League, and the Congress of Racial Equality, as well as organizations such as the National Association of Colored Women's Clubs. Religious groups, including black churches and the Nation of Islam, are also considered.